Three dimensional acoustic tweezers with vortex streaming - Junfei Li (Nature Portfolio, 2021)
Although acoustic and optical tweezers are widely used, it is challenging to create a 3D trap with a simple set-up. Here, acoustic vortex streaming is combined with radiation force to realise 3D trapping of particles in a fluid.